The Effectiveness of the Role of Lead Teachers in Implementing Independent Curriculum-Based Learning to Improve Students' Learning Outcomes and Scientific Literacy Understanding Skills - Ewisahrani, Ewisahrani; Anita, Anita; Nursaban, Eva (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study investigates the effectiveness of the Guru Penggerak program in implementing the Independent Curriculum to improve students’ learning outcomes and scientific literacy. Conducted at SMPN 1 Wera, Bima Regency, the research applied pre-test, post-test, and N-gain analysis, supported by simple linear regression.The findings indicate that the experimental class achieved a higher average score (82.05%) compared to the control class (61%), with an average N-gain of 0.514 (medium category). Regression analysis showed no significant effect of pre-test on post-test (p = 0.176), suggesting that improvements were mainly driven by the role of Guru Penggerak through innovative teaching strategies.In conclusion, the Guru Penggerak effectively enhanced students’ learning outcomes and scientific literacy under the Independent Curriculum.